Applying an Inducible Expression System to Study Interference of Bacterial Virulence Factors with Intracellular Signaling - Berens, Christian; Bisle, Stephanie; Klingenbeck, Leonie; Lührmann, Anja (Journal of Visualized Experiments, 2015)
The technique presented here allows one to analyze at which step a target protein, or alternatively a small molecule, interacts with the components of a signaling pathway. The method is based, on the one hand, on the inducible expression of a specific protein to initiate a signaling event at a defined and predetermined step in the selected signaling cascade. Concomitant expression, on the other hand, of the gene of interest then allows the investigator to evaluate if the activity of the expressed target protein is located upstream or downstream of the initiated signaling event, depending on the readout of the signaling pathway that is obtained. Here, the apoptotic cascade was selected as a defined signaling pathway to demonstrate protocol functionality. Pathogenic bacteria, such as Coxiella burnetii, translocate effector proteins that interfere with host cell death induction in the host cell to ensure bacterial survival in the cell and to promote their dissemination in the organism. The C. burnetii effector protein CaeB effectively inhibits host cell death after induction of apoptosis with UV-light or with staurosporine. To narrow down at which step CaeB interferes with the propagation of the apoptotic signal, selected proteins with well-characterized pro-apoptotic activity were expressed transiently in a doxycycline-inducible manner. If CaeB acts upstream of these proteins, apoptosis will proceed unhindered. If CaeB acts downstream, cell death will be inhibited. The test proteins selected were Bax, which acts at the level of the mitochondria, and caspase 3, which is the major executioner protease. CaeB interferes with cell death induced by Bax expression, but not by caspase 3 expression. CaeB, thus, interacts with the apoptotic cascade between these two proteins.
EVALuna2:7695